Технологічні аспекти оптимізації біогазових установок - Скляр, Олександр Григорович; Скляр, Радміла Вікторівна; Комар, Артем Станіславович; Акулов, Вячеслав Дмитрович; Skliar, Oleksandr; Skliar, Radmila; Komar, Artem; Akulov, Viacheslav (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті розглянуто сучасний стан виробництва й використання біогазу в Україні з акцентом на перспективи оптимізації біогазових установок та ефективну утилізацію відходів птахівництва. Проаналізовано основні технологічні аспекти вдосконалення роботи біогазових комплексів, зокрема впровадження високоефективних систем очищення біогазу, оптимізацію процесів ферментації та застосування цифрових технологій для управління установками. Окрему увагу приділено використанню відходів птахівництва як перспективної сировини для біогазових станцій, що дає змогу зменшити екологічне навантаження та підвищити економічну ефективність біоенергетичних проєктів. EN: The article discusses the current state of biogas production and use in Ukraine, with a focus on the prospects for optimizing biogas plants and efficient utilization of poultry waste. The main technological aspects of improving the operation of biogas complexes are analyzed, including the introduction of highly efficient biogas treatment systems, optimization of fermentation processes, and the use of digital technologies for plant management. Particular attention is paid to the use of poultry waste as a promising raw material for biogas plants, which reduces the environmental burden and increases the economic efficiency of bioenergy projects. Comprehensive ways to increase the productivity of biogas plants are proposed, including the use of multi-stage gas purification, improvement of organic waste processing systems, and the use of innovative materials for biofilters. Comprehensive optimization of biogas plants in Ukraine, including process improvement, equipment modernization, automation and development of the regulatory framework, is a key condition for improving biogas quality and reducing energy costs. Particular attention should be paid to efficient technologies for the utilization of poultry waste, as poultry manure is a promising feedstock for biogas production. The development of optimal fermentation regimes for poultry waste, the use of cofermentation, the modernization of heat recovery systems and the introduction of modern control methods will significantly increase the methane yield and economic efficiency of biogas plants. The successful integration of these measures will contribute to Ukraine’s energy independence, reduce negative environmental impacts, and open up new market opportunities in the global renewable energy market.
Technological aspects of optimization of biogas plants
Keywords: біогаз; біогазові установки; утилізація відходів; оптимізація процесів; біоенергетика; очищення біогазу; птахівництво; biogas; biogas plants; waste utilization; process optimization; bioenergy; biogas purification; poultry farming